Additive manufacturing techniques for the production of tissue engineering constructs. (22nd November 2012) - Mota, Carlos; Puppi, Dario; Chiellini, Federica; Chiellini, Emo
Abstract: 'Additive manufacturing' (AM) refers to a class of manufacturing processes based on the building of a solid object from three‐dimensional (3D) model data by joining materials, usually layer upon layer. Among the vast array of techniques developed for the production of tissue‐engineering (TE) scaffolds, AM techniques are gaining great interest for their suitability in achieving complex shapes and microstructures with a high degree of automation, good accuracy and reproducibility. In addition, the possibility of rapidly producing tissue‐engineered constructs meeting patient's specific requirements, in terms of tissue defect size and geometry as well as autologous biological features, makes them a powerful way of enhancing clinical routine procedures. This paper gives an extensive overview of different AM techniques classes (i.e. stereolithography, selective laser sintering, 3D printing, melt–extrusion‐based techniques, solution/slurry extrusion‐based techniques, and tissue and organ printing) employed for the development of tissue‐engineered constructs made of different materials (i.e. polymeric, ceramic and composite, alone or in combination with bioactive agents), by highlighting their principles and technological solutions. Copyright © 2012 John Wiley & Sons, Ltd.